A influência do Método Pilates sobre a capacidade funcional, a qualidade de vida e a remodelação óssea em mulheres idosas - Sabatini, Nathalia Regina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: Aging is accompanied by a series of physical-emotional changes that have profound impact on individuals’ life. Among these changes we highlight the chronic degenerative diseases such as osteoporosis. The osteoporosis, and its resulting fractures, with high frequency and morbidity, represents a public health problem in several countries, including Brazil. The problem is particularly relevant in women, considering the additional changes observed with the advent of menopause. Physical activity is recognized as a therapeutic tool in these cases, both physically and psychologically. However, considering the relative weakness of this age group, we must be cautious about the various types of exercises, since they can result in potentially serious injury. In this context, Pilates is shown as a system of dynamic exercises, which aims to work strength and flexibility, which imply a better functional ability. Besides, it is individualized process because allows for greater care and interaction between teacher and student, which could lead to more satisfactory results and lower risk. Objective: The objective of this study was to evaluate, in a group of elderly women, the effects of a program of physical exercises based on the Pilates method on functional capacity, quality of life and markers of bone turnover. Cases and Methods: This was a longitudinal, prospective study with intervention, with 40 females, aged 60 or older, enrolled in the Open University of the Third Age of the University of the Sacred Heart (UATI / USC), in Bauru, São Paulo. Two groups of women, one undergoing an exercise program based on Pilates (PEBMP; Pilates group) and other doesn’t, called Control group, were compared before and after application of PEBMB, as the parameters related to functional capacity, quality of life and markers of bone turnover. Functional capacity was assessed by tests of flexibility (sit and reach test) muscle strenght ...

Introdução: O envelhecimento é acompanhado por uma série de alterações físico-emocionais que apresentam profundo impacto na vida dos indivíduos. Entre essas alterações, destacam-se as doenças crônico-degenerativas, tais como a osteoporose. A osteoporose e as fraturas dela resultantes, por sua elevada frequência e morbidade, representam um problema de saúde pública em vários países, incluindo o Brasil. O problema é particularmente relevante em mulheres, considerando-se as mudanças adicionais observadas com o advento da menopausa. A atividade física é reconhecida como uma ferramenta terapêutica nesses casos, tanto do ponto de vista físico como do psicológico. Porém, considerando-se a relativa fragilidade desse grupo etário, há que ter cautela com os vários tipos de exercícios, uma vez que alguns deles podem resultar em lesões potencialmente graves. Nesse contexto, o Método Pilates apresenta-se como um sistema de exercícios dinâmico, que visa trabalhar força e flexibilidade, as quais implicam uma melhor capacidade funcional. Além disso, por se tratar de processo individualizado, permite cuidado e interação maiores entre professor e aluno, o que poderia levar a resultados mais satisfatórios e a menor risco. Objetivo: O objetivo deste estudo foi avaliar, em um grupo de mulheres idosas, os efeitos de um programa de exercicios físicos, baseado no método Pilates, sobre a capacidade funcional, a qualidade de vida e os marcadores de remodelação óssea. Casuística e Métodos: Foi realizado estudo longitudinal, prospectivo, com intervenção, com 40 indivíduos do sexo feminino, com 60 anos ou mais de idade, matriculados na Universidade Aberta à Terceira Idade da Universidade do Sagrado Coração (UATI/USC), da cidade de Bauru, estado de São Paulo. Dois grupos de mulheres, um submetido a programa de exercícios baseado no Método Pilates (PEBMP; grupo Pilates) e outro não (grupo Controle), foram comparados entre ...
Keywords: Pilates, Método; Envelhecimento; Mulheres idosas - Doenças; Ossos - Doenças; Osteoporose; Exercícios físicos